Immune thrombocytopenia in adolescents and young adults - Schifferli, Alexandra (Frontiers in Medicine, 2025)
Previous guidelines for the treatment of immune thrombocytopenia (ITP) have traditionally focused on a dichotomy between pediatric and adult ITP. Adolescents and young adults (AYAs) do not neatly fit into either the pediatric or adult ITP group. A deeper understanding of ITP’s natural history, risk factors for chronicity, and outcomes in AYAs is a crucial first step toward developing tailored treatment algorithms. Such data could form the basis for recommendations targeting this underrepresented yet clinically distinct population. Ultimately, age-adapted trials may improve long-term outcomes, reduce toxicity, and enhance quality of life for AYAs with ITP. The AYAs collaboration—drawing on data from the Pediatric and Adult Registry on Chronic ITP (PARC-ITP), Registre Midi- Pyrénéen-France (CARMEN-France) adult registry in Toulouse, and the National Prospective Cohort for Children with Chronic Autoimmune Cytopenia (OBS’CEREVANCE) in Bordeaux, France—aims to address the information gap in AYAs with ITP. To date, four analyses have been undertaken (using data from 2004 to 2021), each addressing the major clinical aspects of ITP in patients aged 12–25 years: (1) newly diagnosed ITP, (2) chronic disease, (3) refractory courses, and (4) secondary (sITP) forms.